EFFECT OF INFLATION, INTEREST RATE / BI RATE, AND RUPIAH EXCHANGE RATE ON INDONESIAN COMPOSITE INDEX (IDX) AT INDONESIAN STOCK EXCHANGE (ISE) - Resista Vikaliana (STIE Binaniaga, 2017)
Capital market has a strategic role for strengthening the economic resilience of the country and as an alternative for profitable investment. Capital market has an important role in economics of the country due to the dual functions, economics function and finance. Capital market is a national driving force through its role as a source of financing for the company and alternative for investor to invest. In capital market, Indonesia important role as this index can be used as barometer on the economic health of the country. Macroeconomics factor is high inflation, interest rate, and depreciation of rupiah to dollar, could lower the stock price. The aim of this research is to study the effect of macro economy e.g. inflation, rupiah exchange rate, and interest rate on Indonesian Composite Index (IDX) at Indonesian Stock Exchange (ISE).Method of analysis is carried out using linear regression model equation. Data used in this study is secondary monthly data during the period of 2013-2016. Total number of 36 samples is used. The effect of inflation, interest rate / BI Rate and exchange rate to ISE on model equation is 41.61%. Correlation between variable inflation and interest rate / BI rate is 0.490 quite strong at the same direction. Correlation between inflation and exchange rate is -0,349 which is quite strong but not at the same direction. Correlation between interest rate and exchange rate is 1 which is very strong and at the same direction. From the calculation, calculated F < F table (1.825 < 8,92), which can be concluded that there is no linear correlation between inflation, interest rate / BI Rate and exchange rate to ISE. Structural equation is Y= -0.088 X1 -0.300 X2 + 0,165 X3 + Ɛ.Keywords: Inflation, currency, interest rate, ISE